Life-Cycle and Health Impact Analysis of Biodegradable Versus Conventional Medical Supplies: A Novel Comparative Study on Environmental Footprint and Worker Exposure - Harlis Setiyowati; Irfan Maulana; G Thippanna (Green Health International Journal of Health Sciences Nursing and Nutrition, 2024)
The increasing use of conventional medical supplies has led to significant environmental challenges due to waste accumulation and the chemical exposure risks faced by healthcare workers. Despite ongoing efforts to adopt environmentally friendly materials, there is a lack of comprehensive studies that combine Life-Cycle Assessment (LCA) with direct monitoring of worker exposure. This study aims to compare the environmental and health impacts of biodegradable versus conventional medical supplies by assessing their life-cycle stages, energy consumption, carbon footprint, and hazardous exposure risks. A novel comparative approach was adopted, integrating LCA to evaluate raw material extraction, production, usage, and disposal processes, alongside monitoring the occupational exposure to chemical residues from medical supplies. The results indicate that biodegradable medical supplies reduce environmental footprint by approximately 40%, lower energy consumption, and generate less waste compared to conventional plastics. Additionally, the study shows that biodegradable materials pose a significantly reduced risk of chemical exposure to healthcare workers, offering a safer alternative. However, biodegradable materials present limitations, such as availability, durability, and higher initial costs, which need to be addressed for widespread implementation. The findings emphasize the importance of integrating sustainable practices in healthcare settings, offering actionable insights for hospital management and regulatory bodies. Future research is recommended to further explore the cost-effectiveness of biodegradable materials, conduct large-scale trials, and investigate alternative material types. This study contributes to the growing body of knowledge on environmental sustainability and occupational safety in healthcare, providing a valuable framework for future policy and operational decisions.